P826 Economic impact of inflamatory bowel disease in Catalonia. A population-based analysis. (30th January 2023) - Brunet, E; Melcarne, L; Llovet, L P; Garcia-Sague, B; Vela, E; Cleries, M; Pontes, C; García-Iglesias, P; Puy, A; Villoria, A; Calvet, X
Abstract: Background: Background: Inflammatory Bowel Disease (IBD) has an important economic impact in healthcare costs and resources utilization. Population data on this topic are scarce. The aim of this study was to evaluate the current healthcare expenditures of IBD in a population-wide study Catalonia. Methods: Methods: All patients with IBD included in the Catalan Health Surveillance System (CHSS) were included. CHSS includes data on more than 7 million individuals in 2020, 34, 823 of them being diagnosed of IBD. Data on prevalence, incidence, comorbidities, stratification of risk, use of healthcare resources and economic impact were extracted from the CHSS according to ICD-10-CM codes. Health expenditure was calculated according to the standard costs of each service provided by the Department of Health (Generalitat de Catalunya). The utilization of healthcare services and associated expenditure of IBD were compared with a control group of patients not identified as IBD adjusted by age, sex, and income level (hereinafter referred to as "non-IBD"). IBD costs were separately provided for Crohn's Disease (CD) and Ulcerative Colitis (UC). Results: Results: The prevalence and incidence of IBD in 2020 was 405.6 and 27.2 per 100, 000 inhabitants, respectively. Total number of IBD patients in 2020 was 37, 381. Prevalence of comorbidities (neoplasia, arthritis, chronic obstructive pulmonary disease, asthma, cardiac disease, ictus and mental disease) was higher in IBD patients' when compared to non-IBD population. The risk of hospitalization in IBD was twice those of the non-IBD individuals. The global healthcare expenditures of patient with IBD was 164M€. The average annual expenditure for an IBD patient was 4M€ versus 1M€ for non-IBD population; being more than 3.4-fold higher. Cost in UC was 3, 360€ and 5, 699€ for CD patient. Conclusion: Conclusion: Patients with IBD presented a higher risk of comorbidities (1.5-2 fold) and healthcare resources utilization. Healthcare expenditure per patient were approximately 3.4 times higher than the non-IBD population.